ANALISIS KOMPRATIF EKSPETASI PELANGGAN, CITRA TOKO DANKEPUASANPELANGGAN PADA TOKO SPESIAL DIPEKANBARU - Yudianti, Dewi; Indarti, Sri (Jurnal Tepak Manajemen Bisnis, 2016)
Analysis Comparative of Customerâs Expectation, Store Image And Customer SatisfactionAt Special Store In Pekanbaru. Leadered by Sri Indarti and Lilis Sulistyowati ,This research waspurposed to know store image at Ace hardware, Global bangunan and Batam elektronik to lookdifference and comparison of customerâs expectation, store image and customerâs satisfaction atspecial store : Ace Hardware, Global Bangunan and Batam Elektronik.The collection of dataquestioner, divided into 150 respondents with every store was 50 respondent that took with methodepurposive sampling. Data analysis used factor analysis and analysis variance Anova by SPSS 17.Theresult of the research indicate that formed six dimensions store image in every special store byanalysing factor. Based on analyzsis Anova and Poshoc test, Variable of cutomerâs expctation didnotexist difference of perception respondent, whlie variable of store image and customerâs satisfactionexisedt difference significantly at perception respondent between three special store.The comparisonof every atribute at there special store has quality at items that different such as Ace hardware hasneccessity, Global bangunan has seller attitude and Batam elektronik has strategic location. Whilemost quality were compared two spesial store is Global bangunan.